Cloaca‐ and feather‐associated bacteria communities in common waxbills Estrilda astrild. (19th May 2022) - Silva, Sofia Marques; Trigo, Sandra; Cardoso, Gonçalo C.; Xavier, Raquel
Abstract : Host‐associated microbial communities are essential for host homeostasis and health. Most research on microbiotas is restricted to model host species and, since microbe–host dynamics can be species‐specific, we still lack a good taxonomic, ecological and evolutionary understanding of microbiotas in wild hosts, including birds. Given the diversity of avian host species, their habitat specializations, ecological requirements and life‐history traits, we need to characterize the dynamics of microbiotas from taxonomically diverse bird species. Here we describe cloaca and feather microbiotas of a population of common waxbills Estrilda astrild living in a large open‐air mesocosm, and compare it to microbiotas sampled one year later for a subset of this population, and to the microbiotas of free‐ranging waxbills from the same region. We found clear differences between microbiota from the cloaca, which contained some taxa that may be found in seeds, and from feathers, which contained some taxa that have been previously found in plants and soil. We found limited evidence for sexual differences in both cloaca and feather microbiotas, likely due to the gregariousness, similar behaviour and habitat use of both male and female waxbills. Microbial diversities of waxbills from the mesocosm were representative of those found in free‐ranging individuals. Also, structural differences between microbiota from mesocosm and free‐ranging waxbills seemed to be small and comparable to differences found in microbiota from the mesocosm in consecutive years. These results indicate that this mesocosm population could be used as a model in future studies investigating microbiota–host dynamics.